Peran Lagu Populer Simalungun dalam Upacara Adat Perkawinan: Analis Tekstual dan Musikal di Kelurahan Pematang Raya, Kecamatan Raya, Kabupaten Simalungun - Purba, Zulkifli; Dewi, Heristina; Sitopu, Sapna (Jurnal Pendidikan dan Penciptaan Seni, 2025)
This study analyzes the role of Simalungun popular songs in traditional wedding ceremonies in Pematang Raya Village through textual and musical approaches. The research focuses on three main songs: Sitalasari, Etah Mangalop Boru, and Horas Sayur Matua. A qualitative descriptive method was applied using observation, interviews, and documentation techniques. The findings reveal that Simalungun popular songs function as a medium of cultural communication, a form of prayer and blessing, and a symbol of respect toward social structures and customary values. Musically, the songs use diatonic major scales, moderate tempos (85–100 bpm), and simple rhythmic patterns that reflect the sacred and harmonious atmosphere of the ceremony. The transformation from traditional instruments such as gondrang bolon to modern ones like keyboards and guitars does not diminish their cultural meaning. Instead, these songs embody a creative adaptation that preserves traditional values while embracing modern influences. They play a vital role in maintaining Simalungun cultural identity, strengthening social cohesion, and ensuring the continuity of local traditions amid modernization.